Enhancing social capital in communities to manage HIV and AIDS : the role of social workers in the Johannesburg and Ekurhuleni Metropolitan Municipalities - Geyer, Stephan (University of Pretoria, 2014)
Dissertation (MA)--University of Pretoria, 2014.